Reflexiones en torno a la interculturalidad - Diez, María Laura (Cuadernos de antropología social)
Interculturality in education has become an unavoidable discourse, particularly in contexts where socio-political conflicts are directly or indirectly associated with the coexistence of diverse cultural identities in one single social space. In Latin America, the debate usually revolves around cultural diversity as defined by ethnic difference, in terms of indigenous populations or originary peoples, often entailing static and essentialist categories of identity and culture. The aim of this paper is to explore openings and limitations of the intercultural perspective in education, considering its antecedents and the different subject positions which configure the field of dispute in the construction of an intercultural project. The discussion presents a theoretical approach to the problem illustrated by references to concrete ethnographic situations.